2019
DOI: 10.1590/fst.28018
|View full text |Cite
|
Sign up to set email alerts
|

Some physico-chemical properties, fatty acid compositions, macro-micro minerals and sterol contents of two variety tigernut tubers and oils harvested from East Mediterranean region

Abstract: This research on Yellow sugar and Honey tuber varieties tigernut tubers' oils physico-chemical properties were investigated to collected from Adana province in Turkey. The 1000 seed weight, width, length, moisture, ash and ascorbic acid values of yellow sugar and honey wax tubers were established as 343,496 and 327,524 g, 7.61 and 8.76 mm, 17.07 and 15.23 mm, 6.41 and 6.45%, 1.19 and 1.38% and 67.34 and 58.81 mg/kg, respectively. Free fatty acidity, peroxide values, refractive index, density, iodine number, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
5
17
0
Order By: Relevance
“…
Tigernut (Cyperus esculentus L.), native to northeast Africa, belongs to the sedge family (Babiker et al, 2021). It is an important multipurpose crop, its stems and leaves can be used as green feed and knitting materials, and the roots with a fragrant smell are a potential source of essential oils (Duman, 2019;Lasekan, 2013;Ozcan et al, 2021). Tigernut tubers are rich in lipids, proteins, starches, dietary fibers, and vitamins, which are usually applied to develop edible oil, plant milk, and snack food (Clemente-Villalba et al, 2021;Oluwajuyitan & Ijarotimi, 2019).The extraction and physicochemical characterization of tigernut tuber oil have been widely reported (Aljuhaimi, Ghafoor, et al, 2018; Aljuhaimi, Simsek, & Ozcan, 2018).
…”
mentioning
confidence: 99%
“…
Tigernut (Cyperus esculentus L.), native to northeast Africa, belongs to the sedge family (Babiker et al, 2021). It is an important multipurpose crop, its stems and leaves can be used as green feed and knitting materials, and the roots with a fragrant smell are a potential source of essential oils (Duman, 2019;Lasekan, 2013;Ozcan et al, 2021). Tigernut tubers are rich in lipids, proteins, starches, dietary fibers, and vitamins, which are usually applied to develop edible oil, plant milk, and snack food (Clemente-Villalba et al, 2021;Oluwajuyitan & Ijarotimi, 2019).The extraction and physicochemical characterization of tigernut tuber oil have been widely reported (Aljuhaimi, Ghafoor, et al, 2018; Aljuhaimi, Simsek, & Ozcan, 2018).
…”
mentioning
confidence: 99%
“…They also could be named pinellic acid isomers, according to Ruan et al (2019), who described them in Pluchea indica aerial parts [26]. Peaks 37-40 and 42-45 were identified as fatty acids, linolenic, myristic, palmitoleic, linoleic, palmitic, oleic, heptadecanoic, and stearic, according to several authors that found them in tiger nut oil [27][28][29]. Hydroxyoleic acid isomers (peaks 31-33, 35) and dihydroxyoleic acids isomers (peaks [23][24][25][26], derived from oleic acid, have also been found.…”
Section: Identification Of Polar Compounds By Hplc-esi-tof-msmentioning
confidence: 99%
“…The free acidity in honey is present due to polyphenol, ascorbic acid, and amino groups. 24 The fermentation process of sugar into organic acids results in an increase in the honey acidity degeneration. The free acidity value of FHs honey samples (16.8 ± 4.97) and BHs honey samples (19.0 ± 2.34) samples (Table 1) were within the International limits of not more than 50 meq/kg.…”
Section: Free Acidity Of Honeysmentioning
confidence: 99%